2007
DOI: 10.1016/j.jvs.2007.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal Artery Aneurysm with Acute Ischemia in 229 Patients. Outcome after Thrombolytic and Surgical Therapy

Abstract: Objectives This study investigated the relationship between annual hospital volume and the outcomes in carotid endarterectomy and quantified critical volume threshold for this procedure.Data sources PubMed, EMBASE and the Cochrane library were searched for all articles on the volume-outcome relationship in CEA.Review methods Articles were included if they presented data on post-operative mortality and/or stroke rates and annual hospital volume of CEA. The review conformed to the QUOROM statement. The data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Ravn et al 1 reported 571 patients with 717 legs treated in Sweden in 1987e2002: preoperative thrombolysis improved run-off and reduced the risk of amputation when the patient presented with acute ischaemia, 2 and open repair (OR) with a posterior approach (often using the inlay technique) had better long-term results because of the reduced risk of late expansion. 3 It was not meaningful to compare OR and endovascular repair (ER) during this time period.…”
Section: Introductionmentioning
confidence: 99%
“…Ravn et al 1 reported 571 patients with 717 legs treated in Sweden in 1987e2002: preoperative thrombolysis improved run-off and reduced the risk of amputation when the patient presented with acute ischaemia, 2 and open repair (OR) with a posterior approach (often using the inlay technique) had better long-term results because of the reduced risk of late expansion. 3 It was not meaningful to compare OR and endovascular repair (ER) during this time period.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the prevalence of multi-aneurysmal disease already existed in 1092 of the 1509 patients (72%), a result of previous investigations in 1987-2002 1,3,4 and 2008e 2012. 7 To study the frequency of multi-aneurysmal disease among the women operated on in 2003e2007, questionnaires were sent to the treating hospitals, asking about any diagnosis of additional aneurysmal disease and amputation until June 2012.…”
Section: Methodsmentioning
confidence: 91%
“…28,29 PAAs often generate emboli that progressively occlude the distal arterial network, making thrombolysis a valuable first line approach, which later in elective settings can be followed by surgical repair of the aneurysm. 29,30 The poor patency rate after thrombolysis for occluded PAA, might be explained by incomplete runoff clearance of fresh and/or old embolic clots. This subgroup, however, had the best amputation free survival at 5 years and higher survival after 5 years.…”
Section: Discussionmentioning
confidence: 99%